2022
DOI: 10.3390/nano12040665
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for the Direct and Alternating Current-Driven Electrospinning of Polyamides

Abstract: The paper provides a description of the potential for the direct current- and alternating current-driven electrospinning of various linear aliphatic polyamides (PA). Sets with increasing concentrations of selected PAs were dissolved in a mixture of formic acid and dichloromethane at a weight ratio of 1:1 and spun using a bar electrode applying direct and alternating high voltage. The solubility and spinnability of the polyamides were investigated and scanning electron microscopy (SEM) images were acquired of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Cyclic nature of nanofiber generation, often different precursor requirements than in DC electrospinning, and slowly propagating dense fibrous flows in AFES allow expansion of the possible polymeric precursor systems, handling approaches of the generated nanofibers, and structure and textural properties of the resulting nanofibrous materials. [10][11][12][13] Lawson et al 14 have shown that AFES of PCL can efficiently work with acetic acid as the only solvent, or with multi-solvent systems based on mixtures of formic acid, acetic acid, and acetone, as demonstrated by Sivan et al 15 The PCL nanofibers productivity rates between 1.0 and 12.4 gÁh À1 were obtained depending on the solvent system and applied AC voltage. Varying the process parameters, such as AC frequency and solvent system, allows for modification of the resulting PCL nanofibrous material characteristics like wettability, contact angle, density, alignment, and surface energy.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Cyclic nature of nanofiber generation, often different precursor requirements than in DC electrospinning, and slowly propagating dense fibrous flows in AFES allow expansion of the possible polymeric precursor systems, handling approaches of the generated nanofibers, and structure and textural properties of the resulting nanofibrous materials. [10][11][12][13] Lawson et al 14 have shown that AFES of PCL can efficiently work with acetic acid as the only solvent, or with multi-solvent systems based on mixtures of formic acid, acetic acid, and acetone, as demonstrated by Sivan et al 15 The PCL nanofibers productivity rates between 1.0 and 12.4 gÁh À1 were obtained depending on the solvent system and applied AC voltage. Varying the process parameters, such as AC frequency and solvent system, allows for modification of the resulting PCL nanofibrous material characteristics like wettability, contact angle, density, alignment, and surface energy.…”
mentioning
confidence: 95%
“…alternating current (AC) electrospinning) has gained traction in recent years as a high‐yield, sustainable approach to nanofiber production. Cyclic nature of nanofiber generation, often different precursor requirements than in DC electrospinning, and slowly propagating dense fibrous flows in AFES allow expansion of the possible polymeric precursor systems, handling approaches of the generated nanofibers, and structure and textural properties of the resulting nanofibrous materials 10–13 . Lawson et al 14 have shown that AFES of PCL can efficiently work with acetic acid as the only solvent, or with multi‐solvent systems based on mixtures of formic acid, acetic acid, and acetone, as demonstrated by Sivan et al 15 The PCL nanofibers productivity rates between 1.0 and 12.4 g∙h −1 were obtained depending on the solvent system and applied AC voltage.…”
Section: Introductionmentioning
confidence: 99%